Afmeting excl. passe-partout. . Titel prent: F.W.N. Hugenholtz. . BG PM1/20-6 is andere versie van deze tekening - Hahn, Albert,
Afmeting excl. passe-partout. Titel prent: F.W.N. Hugenholtz. BG PM1/20-6 is andere versie van deze tekening.